Evaluating immunological and inflammatory changes of treatment-experienced people living with HIV switching from first-line triple cART regimens to DTG/3TC vs. B/F/TAF: the DEBATE trial - Cossarizza, Andrea; Cozzi-Lepri, Alessandro; Mattioli, Marco; Paolini, Annamaria; Neroni, Anita; De Biasi, Sara; Tartaro, Domenico Lo; Borella, Rebecca; Fidanza, Lucia; Gibellini, Lara; Beghetto, Barbara; Roncaglia, Enrica; et al. (Frontiers in Immunology, 2023)
The aim of this randomized clinical trial (RCT) was to compare immunological changes in virallysuppressed PLWH switching from a three-drug regimen (3DR) to 3DR or a 2DR.An open-label, prospective RCT enrolling PLWH receiving a 3DR who switched to B/F/TAF or DTG/3TC.Blood was taken at baseline and at month 6 and 12. The primary outcome was the change in CD4+ or CD8+ T cell counts, CD4/CD8 ratio over time points. Secondary outcomes were the changes in immunological and inflammatory parameters. A parametric mixed-linear models with random intercept and slopes were fitted separately for each marker after controlling for potential confounders.Between 2 arms (33 PLWH each) there was no difference in CD4+ or CD8+ T-cells, CD4/CD8 ratio and IL-6 trajectories. PLWH switching to DTG/3TC had increased levels of both transitional memory and terminally differentiated CD4+ T-cells (arm-time interaction p-value=0.02) and to a less extent for the corresponding CD8+ T-cell subsets (p=0.09). A significantly lower levels of non-classical monocytes were detected in B/F/TAF arm at T6 (diff =-6.7 cells/mm3, 95% CI; -16;+2.6; p-value for interaction between arm and time 0.03). All differences were attenuated at T12.No evidence for a difference in absolute CD4+ and CD8+ T-cell counts, CD4/CD8 ratio and IL-6 trajectories by study arm over 12 months was found. PLWH on DTG/3TC showed higher levels of terminally differentiated and exhausted CD4+ and CD8+ T-lymphocytes and nonclassical monocytes at T6. Further studies are warranted to better understand the clinical impact of our results.